Evaluation of different times application of Methomyl 90% insecticide for the control of the fall armyworm (Spodoptera frugiperda) in the maize crop - Vélez, Mayra (2021)
The fall armyworm (Spodoptera frugiperda) is one of the most destructive pests for the maize crop, its control is based on highly dangerous insecticide applications. The use of Economic thresholds (ET’s) indicates the moment when control actions should be initiated to prevent pests from reaching levels of economic damage, their application generally results in the reduction of the number of pesticide applications. In Ecuador, the use of ET’s for the control of the fall armyworm is not considered, which causes a series of damages in the agroecosystems. In this research, different application times of the Methomyl 90% insecticide for the control of the fall armyworm were evaluated, and the behavior of growth and production variables of corn plants was also verified. The application of the Methomyl 90% insecticide did not influence the variables of plant height, number of ear rots, ear rot diameter, ear rot length, number of rows per ear rots. However, it was possible to recognize its influence on the incidence of the fall armyworm, damage severity, and corn yields. T1 (application of insecticide 15 days after planting) and T2 (application of insecticide based on the ET of 25% of plants with damage) obtained the lowest percentage severity of the damage, also had the highest corn yields, 5754.11 kg/ha and 6609.51 kg/ha respectively. The results obtained show that the use of the ET of 25% did not compromise the yield of the corn crop, also, it allowed the reduction of unnecessary applications of insecticides.